2016
DOI: 10.5935/1415-2762.20160044
|View full text |Cite
|
Sign up to set email alerts
|

The Play Therapy and Child Hospitalized in Perspective of Parents

Abstract: RESUMOA hospitalização traz transtornos que, na infância, tornam-se mais evidentes nas manifestações de insatisfação momentânea ou prejuízos, podendo permanecer mesmo após a alta hospitalar. Na Pediatria as crianças são submetidas a procedimentos dolorosos, além de depararem com situações variadas como a presença constante de pessoas estranhas ao seu convívio habitual, como profissionais de saúde de diversas áreas, outros pacientes internados e seus acompanhantes. Nesse cenário, a aplicação da ludoterapia no m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 6 publications
1
1
0
11
Order By: Relevance
“…A research study carried out in a pediatric unit in Brazil showed that the mothers feel calmer when experiencing playfulness with their children, who showed signs of distraction, overcoming, and understanding regarding hospitalization. This finding also converges with the data from the present study, which confirm the benefits of using the game as a facilitator in the process of coping with hospitalization and as an information vehicle (17) .…”
Section: Discussionsupporting
confidence: 91%
“…A research study carried out in a pediatric unit in Brazil showed that the mothers feel calmer when experiencing playfulness with their children, who showed signs of distraction, overcoming, and understanding regarding hospitalization. This finding also converges with the data from the present study, which confirm the benefits of using the game as a facilitator in the process of coping with hospitalization and as an information vehicle (17) .…”
Section: Discussionsupporting
confidence: 91%
“…According to a study carried out with mothers of hospitalized children, 96.8% reported that the preferred place of their hospitalized children was the toy library. 19 It was reported by the mothers as positive points related to the use of games, that there is a relieving of suffering and tensions that are generated by the hospitalization, leaving the child calmer, reducing the negative effects and helping in the development of the child, since some pedagogical activities offered help both with learning and in the development of physical and psychological abilities and they also favor interaction, where children know each other and play with each other. It is also believed that play serves as a palliative in the hospitalization situation, besides offering positive points related to the disease, allowing the child to live situations common to their daily life.…”
Section:  View Of the Companions In Relation To The Play Activitiesmentioning
confidence: 99%
“…A hospitalização traz diversas alterações na rotina comum das crianças e suas famílias, permitindo o surgimento de transtornos que irão afetar o seu desenvolvimento. 1 O processo de permanência no ambiente hospitalar é relatado como um evento que afeta a criança, podendo trazer à tona angústias e medos que antes não existiam em seu cotidiano. 2 Procedimentos dolorosos, exames repetitivos e exaustivos fazem com que a mesma desenvolva respostas que não são comuns ao seu comportamento tradicional, como agressividade, ansiedade, apatia, estados depressivos, fobias e distúrbios de sono e alimentação.…”
Section: Introductionunclassified
“…[3][4] Quando não manejada de forma apropriada, a internação é capaz de causar impactos à criança que perduram após a alta, comprometendo o seu desenvolvimento e podendo, inclusive, interferir na sua vida adulta. 1 O brincar, por sua vez, constitui estágio importante na vida de uma criança capaz de moldar o seu desenvolvimento físico, verbal e intelectual, proporcionando-lhe um bem-estar geral e a melhora de fatores como comunicação, estímulo à interação, relacionamento interpessoal, convívio em grupo, apreensão de procedimentos e aceitação de normas. [1][2]5 No Brasil, baseando-se na importância do ato mencionado para a faixa etária pediátrica, em 24 de março de 2005, o Congresso Nacional aprovou a Lei nº 11.104, que tornou possível a idealização da brinquedoteca hospitalar.…”
Section: Introductionunclassified
See 1 more Smart Citation